A structure of training workloads in race walking. Different stages of athlete's development in case of four-year perparation to the Olympic Games in Beijing - Ozimek, M.; Augustyn, K.; Augustyn, R. (Lambert Academic Publishing, 2015)
Present book is targeted at various body of readers - performance athletes, teachers, coaches and researchers. This work engages theoretically and practically significant question which describes and compares workloads structures in race walking of sportsmen being at different stages of development in the light of 4-year-long preparation for the 2008 Olympic Games in Beijing. Authors interestingly attempted to follow athletic periodization, in which crucially important training periods were investigated within professional career at the age of junior, u23 and senior as well as, additionally, 4-year Olympic cycle between 2005 and 2008. In concrete and unambiguous way it focuses on volume (km) and intensity (aerobic, aerobic-anaerobic, anaerobic-aerobic resources) of completed training work and its association with the final results achieved by the athlete at 20km distance. Moreover, to analyze race walker preparation and latter effect control, each of the seasons involved in this research was finished with elite level event in given age category, but the target and the most high-ranking competitions were the 2008 Olympic Games in Beijing